2010
DOI: 10.1063/1.3498806
|View full text |Cite
|
Sign up to set email alerts
|

Band structure of phononic crystals with general damping

Abstract: In this paper, we present theoretical formalisms for the study of wave dispersion in damped elastic periodic materials. We adopt the well known structural dynamics techniques of modal analysis and state-space transformation and formulate them for the Bloch wave propagation problem. First, we consider a one-dimensional lumped parameter model of a phononic crystal consisting of two masses in the unit cell whereby the masses are connected by springs and dashpot viscous dampers. We then extend our analysis to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(78 citation statements)
references
References 25 publications
3
75
0
Order By: Relevance
“…It was also shown that viscoelasticity did not only attenuate acoustic waves traversing a rubber-based phononic crystal but also modified the frequency of passing bands in the transmission spectrum [43]. A theory of damped Bloch waves [44] was employed to show that damping alters the shape of dispersion curves and reduces the size of band gaps as well as opens wave vector gaps via branch cutoff [45]. Loss has an effect on the complete complex band structure of phononic systems including the group velocity [46].…”
Section: Dissipative Mediamentioning
confidence: 99%
“…It was also shown that viscoelasticity did not only attenuate acoustic waves traversing a rubber-based phononic crystal but also modified the frequency of passing bands in the transmission spectrum [43]. A theory of damped Bloch waves [44] was employed to show that damping alters the shape of dispersion curves and reduces the size of band gaps as well as opens wave vector gaps via branch cutoff [45]. Loss has an effect on the complete complex band structure of phononic systems including the group velocity [46].…”
Section: Dissipative Mediamentioning
confidence: 99%
“…A direct comparison between the geometric features of the regular honeycomb and hierarchical honeycombs leads us to believe that different mechanisms of band gaps formation are intrinsically dictated by the slenderness ratio and coordination number of the lattice. It should be pointed out that damping effect resulting from the viscoelastic feature of the glassy polymer may make some contribution to the wave attenuation [24]. However, recent experimental results indicate that the damping effect will not swamp the band gaps in the phononic dispersion relations [25].…”
Section: Introductionmentioning
confidence: 97%
“…Damping is an interesting tool in further engineering phononic structures [14] to comply with specific needs in complex applications. An interesting example is the case of an fcc crystal of close-packed rubber spheres in air (see Fig.…”
Section: Formation Of Omnidirectional Frequency Gaps Attenuation Anmentioning
confidence: 99%